Diltiazem prevents stress‐induced contractile deficits in cardiomyocytes, but does not reverse the cardiomyopathy phenotype in Mybpc3‐knock‐in mice. (7th February 2017) - Flenner, Frederik; Geertz, Birgit; Reischmann‐Düsener, Silke; Weinberger, Florian; Eschenhagen, Thomas; Carrier, Lucie; Friedrich, Felix W.
Abstract : Key points: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiac illness and can lead to diastolic dysfunction, sudden cardiac death and heart failure. Treatment of HCM patients is empirical and current pharmacological treatments are unable to stop disease progression or reverse hypertrophy. In this study, we tested if the non‐dihydropyridine Ca 2+ channel blocker diltiazem, which previously showed potential to stop disease progression, can improve the phenotype of a HCM mouse model ( Mybpc3 ‐targeted knock‐in), which is based on a mutation commonly found in patients. Diltiazem improved contractile function of isolated ventricular cardiomyocytes acutely, but chronic application did not improve the phenotype of adult mice with a fully developed HCM. Our study shows that diltiazem has beneficial effects in HCM, but long‐term treatment success is likely to depend on characteristics and cause of HCM and onset of treatment. Abstract: Left ventricular hypertrophy, diastolic dysfunction and fibrosis are the main features of hypertrophic cardiomyopathy (HCM). Guidelines recommend β‐adrenoceptor or Ca 2+ channel antagonists as pharmacological treatment. The Ca 2+ channel blocker diltiazem recently showed promising beneficial effects in pre‐clinical HCM, particularly in patients carrying MYBPC3 mutations. In the present study we evaluated whether diltiazem could ameliorate or reverse the disease phenotype in cells and in vivo in an Mybpc3 ‐targeted knock‐in (KI) mouse model of HCM. Sarcomere shortening and Ca 2+ transients were measured in KI and wild‐type (WT) cardiomyocytes in basal conditions (1‐Hz pacing) and under stress conditions (30 nm isoprenaline, 5‐Hz pacing) with or without pre‐treatment with 1 μm diltiazem. KI cardiomyocytes exhibited lower diastolic sarcomere length (dSL) at baseline, a tendency to a stronger positive inotropic response to isoprenaline than WT, a marked reduction of dSL and a tendency towards arrhythmias under stress conditions. Pre‐treatment of cardiomyocytes with 1 μm diltiazem reduced the drop in dSL and arrhythmia frequency in KI, and attenuated the positive inotropic effect of isoprenaline. Furthermore, diltiazem reduced the contraction amplitude at 5 Hz but did not affect diastolic Ca 2+ load and Ca 2+ transient amplitude. Six months of diltiazem treatment of KI mice did not reverse cardiac hypertrophy and dysfunction, activation of the fetal gene program or fibrosis. In conclusion, diltiazem blunted the response to isoprenaline in WT and KI cardiomyocytes and improved diastolic relaxation under stress conditions in KI cardiomyocytes. This beneficial effect of diltiazem in cells did not translate in therapeutic efficacy when applied chronically in KI mice. Key points: Hypertrophic cardiomyopathy (HCM) is the most common inherited cardiac illness and can lead to diastolic dysfunction, sudden cardiac death and heart failure. Treatment of HCM patients is empirical and current pharmacological treatments are unable to stop disease progression or reverse hypertrophy. In this study, we tested if the non‐dihydropyridine Ca 2+ channel blocker diltiazem, which previously showed potential to stop disease progression, can improve the phenotype of a HCM mouse model ( Mybpc3 ‐targeted knock‐in), which is based on a mutation commonly found in patients. Diltiazem improved contractile function of isolated ventricular cardiomyocytes acutely, but chronic application did not improve the phenotype of adult mice with a fully developed HCM. Our study shows that diltiazem has beneficial effects in HCM, but long‐term treatment success is likely to depend on characteristics and cause of HCM and onset of treatment.